Assessment of Serum P53, GPX, SOD and CA15-3 Levels in Breast Cancer Patients Under Treatment: A Cross-sectional Study in Basrah, Iraq - Abbas, Ali Falih; Ali, Dawood Salman; Al-Shawi, Ali A. A. (Asian Pacific Journal of Cancer Biology, 2025)
Objective: This study aimed to evaluate the relationship between tumor protein (P53), glutathione peroxidase (GPx), Super oxide dismutase (SOD), cancer antigen (CA15-3) in breast cancer, as well as the impact of variables such as age, location, duration of Illness, and kind of therapy. Methodology: This case-control study carried out between November 2024 to April 2025, at Sadr Teaching Hospital, Oncology Department and Al-Zubair General Hospital, Basrah, Iraq. A total of 178 participants were chosen as a sample; we chose 89 breast cancer patients as cases and 89 healthy individuals as controls. We measured the levels of P53, GPx, SOD, CA15-3. Results: The study revealed significant differences in P53 levels between patients and healthy controls (P<0.001), associated with age, geographic location, and treatment type, while GPx levels were decreased in patients. No significant differences were observed in SOD or CA15-3 levels. Factors such as geographic location, treatment type, and disease duration had no significant impact on the measured concentrations. Additionally, positive correlations were found between P53 and GPx1, as well as between GPx1 and SOD. Conclusion: Age is a major risk factor for breast cancer. The decreased levels of P53 and GPx1 indicate the role of oxidative stress, highlighting the need to investigate biomarkers and genetic factors to improve disease understanding and management. No significant differences were observed in the other variables.